Testing and Histipathological Description of the Occurrence of Lumpy Skin Disease in Cattle in Kulon Progo, Special Region of Yogyakarta - Andri, Andri; Gustian, Gustian; Agustine, Leony (Baselang, 2023)
LSD disease is caused by the DNA virus of the genus Capripox from the family poxviridae. This disease is transmitted in various ways, one of which is a vector bite. It is suspected that drum flies and wild animals such as rats in drums play a role in spreading this disease within one drum or in a larger area. According to tests that have been carried out and existing theories, this disease is also excreted in livestock products, for example saliva, milk and semen directly, and also spreads indirectly through the use of non-sterile livestock equipment and human power (REF). (search about whether it has gone so far and the samples used and the results at the Wates bbvet. Cases of LSD disease have spread to almost all regions in Java and have been confirmed by the competent ministry. This article contains findings from residents' reports to local agencies who submitted requests for examination starting from physical signs, clinical symptoms, Real Time Polymerase Chain Reaction (RT-PCR) examination as well as histopathological examination of a biopsy of skin tissue where the nodule lesion was formed. RT-PCR examination to confirm the presence of the virus from swab samples and lesion scrapings as well as histopathological examination is carried out to ensure the formation of intracytoplasmic inclusion bends as one of the characteristic features of LSD disease.